Experimental and Theoretical Evaluation of Four NLO‐Active Divalent Transition‐Metal Complexes Supported by an Enantiomerically Pure Tetradentate Schiff Base Ligand. Issue 34 (3rd November 2022) - Celedón, Salvador; Hamon, Paul; Artigas, Vania; Fuentealba, Mauricio; Kahlal, Samia; Ledoux‐Rak, Isabelle; Carrillo, David; Saillard, Jean‐Yves; Manzur, Carolina; Hamon, Jean‐René
Abstract: This paper reports on a series of five chiral Schiff base push‐pull compounds derived from enantiomerically pure (1 R, 2 R )‐(−)‐1, 2‐diaminocyclohexane. The Ni II, Cu II, Zn II and Pd II complexes supported by a ferrocene‐containing unsymmetrically‐substituted N2 O2 quadridentate Schiff base ligand were prepared via template reactions and isolated in 74–87 % yields. A combination of EA, IR, UV/vis and 1 H/ 13 C{ 1 H} NMR spectroscopy, HRMS spectrometry, cyclic voltammetry and single‐crystal X‐ray analysis (for the proligand 2 and its Ni II derivative 3 ), together with computational methods (DFT and TD‐DFT) was used to fully characterize and study the properties of all products. Both 2 and 3 crystallize in the orthorhombic non‐centrosymmetric space group P 21 21 21, with two ( R, R )‐(−)‐chiral carbon atoms in their structure. Second‐order nonlinear polarizabilities β have been measured by using Harmonic Light Scattering at 1.91 μm, with the Pd(II) species showing the higher NLO response of 460×10 −30  esu. Abstract : Chiral push‐pull Ni(II), Cu(II), Zn(II) and Pd(II) Schiff base complexes with asymmetric N2 O2 donor atoms sets were synthesized by template condensation using ferrocenoylacetone, (1 R, 2 R )‐(−)‐1, 2‐diaminocyclohexane and 5‐nitro‐salicylaldehyde as starting materials. Their electrochemical behavior and second‐order NLO properties were investigated along with their analytical, spectroscopic and structural characterizations complemented by DFT and TD‐DFT calculations.